Evidence for a PI3-kinase independent pathway in the regulation of Rap1b activation downstream of the P2Y12 receptor in platelets. (17th November 2022) - Dangelmaier, Carol; Kunapuli, Satya P
Abstract: Platelet activation by adenosine diphosphate (ADP) is mediated through two G-protein-coupled receptors, P2Y1 and P2Y12, which signal through Gq and Gi, respectively. P2Y1 stimulation leads to phospholipase C activation and an increase in cytosolic calcium necessary for CalDAG-GEF1 activation. Engagement of P2Y12 inhibits adenylate cyclase, which reduces cAMP, and activation of PI3-kinase, which inhibits RASA3 resulting in sustained activated Rap1b. In this study we activated human platelets with 2-MeSADP in the presence of LY294002, a PI3-kinase inhibitor, AR-C69931MX, a P2Y12 antagonist or MRS2179, a P2Y1 antagonist. We measured the phosphorylation of Akt on Ser473 as an indicator of PI3-kinase activity. As previously shown, LY294002 and ARC69931MX abolished 2MeSADP-induced Akt phosphorylation. MRS2179 reduced ADP-induced Akt phosphorylation but did not abolish it. Rap1b activation, however, was only reduced, but not ablated, using LY294002 and was completely inhibited by ARC69931MX or MRS2179. Furthermore, 2MeSADP-induced Rap1b activation was abolished in either P2Y1 or P2Y12 null platelets. These data suggest that ADP-induced Rap1b activation requires both P2Y1 and P2Y12. In addition, although stimulation of P2Y12 results in PI3-kinase activation leading to Akt phosphorylation and Rap1b activation, Rap1b activation can occur independently of PI3-kinase downstream of P2Y12. Thus, we propose that the P2Y12 receptor can regulate Rap1b, possibly through RASA3, in a pathway independent of PI3-kinase.